Services trade in ASEAN the road taken and the journey ahead - Neo, Dora Swee Suan; Sauve, Pierre 1959-; STreho, Imola (Integration through law : the role of law and the rule of law in Asean integration, 2019)
"Introduction The Member States of the Association of South East Asian Nations (ASEAN) set themselves the ambitious aim of establishing a region-wide economic community by 2015 and to deepen it in the context of the ASEAN Economic Community Blueprint 2015. In striving to achieve such ambitious objectives, there are strong reasons, both internal to ASEAN's own integration process and linked to the region's deepening ties with a dense layer of external economic partners, to believe that service sector reforms, and trade and investment in services more particularly, will occupy a place of choice in the regiion's policy pantheon. " -- Provided by publisher.